2010
DOI: 10.1088/1742-5468/2010/08/p08026
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation dynamics of stochastic long-range interacting systems

Abstract: Long-range interacting systems, while relaxing towards equilibrium, may get trapped in nonequilibrium quasistationary states (QSS) for a time which diverges algebraically with the system size. These intriguing non-Boltzmann states have been observed under deterministic Hamiltonian evolution of a paradigmatic system, the Hamiltonian Mean-Field (HMF) model. We study here the robustness of QSS with respect to stochastic processes beyond deterministic dynamics within a microcanonical ensemble. To this end, we gene… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…For practical purposes, the Vlasov equation is used as a good approximation for sufficiently large N , its validity being limited for short times. Although the lifetime of a QSS have been extensively studied in the literature [19][20][21][22][23][24][25] many aspects of its physical interpretation and phenomenology remain unclear. In the present paper we discuss how to properly define a timescale for its long-time evolution which is governed by collisional corrections to the Vlasov equation leading to the Landau or Balescu-Lenard kinetic equations (see Ref.…”
Section: Introductionmentioning
confidence: 99%
“…For practical purposes, the Vlasov equation is used as a good approximation for sufficiently large N , its validity being limited for short times. Although the lifetime of a QSS have been extensively studied in the literature [19][20][21][22][23][24][25] many aspects of its physical interpretation and phenomenology remain unclear. In the present paper we discuss how to properly define a timescale for its long-time evolution which is governed by collisional corrections to the Vlasov equation leading to the Landau or Balescu-Lenard kinetic equations (see Ref.…”
Section: Introductionmentioning
confidence: 99%
“…The robustness of quasistationarity to stochastic dynamical processes has also been analyzed, where it is found that QSS exist only as a crossover phenomenon. Under such dynamics, these states have a finite relaxation time which is determined by the rate of the stochastic process [28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to compare our results with related previous work in the literature. In [11,12] the stochastic perturbation applied to the long-range system (the HMF model) permutes the momenta of triplets of particles chosen randomly in the system, and drives the system to relax to thermal equilibrium efficiently. Applied to a one dimensional self-gravitating system, we have checked that we observe the same behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…However, much more generally, it has been suggested on the basis of study of the one dimensional HMF model (see e.g. [11,12]) that QSS will disappear in the presence of any generic stochastic perturbation to the dynamics. A study of the effect of external stochastic fields with spatial correlation applied to the same model (see e.g.…”
Section: Introductionmentioning
confidence: 99%